Physiologic Monitor Alarm Rates at 5 Children's Hospitals. Issue 6 (25th April 2018) - Schondelmeyer, Amanda C.; Brady, Patrick W.; Goel, Veena V.; Cvach, Maria; Blake, Nancy; Mangeot, Colleen; Bonafide, Christopher P.
Abstract : Alarm fatigue has been linked to patient morbidity and mortality in hospitals due to delayed or absent responses to monitor alarms. We sought to describe alarm rates at 5 freestanding children's hospitals during a single day and the types of alarms and proportions of patients monitored by using a point‐prevalence, cross‐sectional study design. We collected audible alarms on all inpatient units and calculated overall alarm rates and rates by alarm type per monitored patient per day. We found a total of 147, 213 alarms during the study period, with 3‐fold variation in alarm rates across hospitals among similar unit types. Across hospitals, one‐quarter of monitored beds were responsible for 71%, 61%, and 63% of alarms in medical‐surgical, neonatal intensive care, and pediatric intensive care units, respectively. Future work focused on addressing nonactionable alarms in patients with the highest alarm counts may decrease alarm rates.